Factors affecting household involvement in recycling activities - Thein, Angelin Lee Ching; Kang, Ying Fong (2018)
Recycling is a process to transform the waste into new product which can reused them again especially for the raw materials. The purpose of this study is to examine the factors affecting household involvement in recycling activities in the location of Kuala Lumpur and Selangor. This study adopted the Theory of Planned Behavior Model (TPB) and Theory of Reasoned Action Model (TRA) to identify the relationship between the independent variables (attitudes, social norms, perceived behavioral control, moral norms) and dependent variable (recycling behavior) towards household involvement in recycling activities. A total of 240 questionnaires have been distributed to the household who currently resident in Kuala Lumpur and Selangor. Besides, the SPSS version 21 was used to analyze the relationship between the independent variables and dependent variable. The findings of this research show that the relationship between perceived behavioral control and moral norms has a positive relationship towards household recycling behavior. In contrast, attitude and social norms has no relationship towards household recycling behavior To conclude this study, the summary of descriptive analysis, discussion of the major findings and the theoretical and managerial implications of the research have been discussed. Lastly, limitation of the study and recommendations for future research are also discussed and highlighted to overcome the problem and potential improvement for the future study.